Progress and prospects in harnessing wild relatives for genetic enhancement of salt tolerance in rice - Padmavathi, Guntupalli; Bangale, Umakanth; Rao, K. Nagendra; Balakrishnan, Divya; Arun, Melekote Nagabhushan; Singh, Rakesh Kumar; Sundaram, Raman Meenakshi (Frontiers in Plant Science, 2024)
Salt stress is the second most devastating abiotic stress next to drought and limits rice production globally. Genetic enhancement of tolerance to salinity is a promising and cost effective approach to achieve yield gains in salt affected areas. Breeding for salinity tolerance is challenging due to the genetic complexity of response of rice plant to salt stress, as it is governed by minor genes with low heritability and high G x E interaction. The involvement of numerous physiological and biochemical factors further compounds this complexity. The intensive selection and breeding efforts targeted towards improvement of yield in the green-revolution era, inadvertently resulted in the gradual disappearance of the loci governing salinity tolerance and also a significant reduction in genetic variability among cultivars. The limited utilization of genetic resources and the narrow genetic base of improved cultivars has resulted in plateauing of response to salinity tolerance in modern cultivars. Wild species are an excellent genetic resources for broadening the genetic base of domesticated rice. Exploiting novel genes of underutilized rice wild relatives to restore salinity tolerance loci eliminated during domestication, can bring significant genetic gain in rice cultivars. Wild species of rice, O. rufipogon and O. nivara, have been harnessed in the development of a few improved rice varieties like Jarava and Chinsura Nona 2. Further, increased access to sequence information and enhanced knowledge about the genomics of salinity tolerance in wild relatives has provided an opportunity for deployment of wild rice accessions in breeding programmes while overcoming the cross-incompatibility and linkage drag barriers witnessed in wild hybridization. Pre-breeding is another avenue to build up the material ready for utilization in breeding programs at a later date. Efforts should be directed towards systematic collection, evaluation, characterization and also deciphering salt tolerance mechanisms in wild rice introgression lines and deploy the untapped novel loci, for improvement of salinity tolerance in rice cultivars. This review highlights the potential of wild relatives of Oryza in enhancing tolerance to salinity, tracks the progress of work and gives a perspective of future research work.